Assessing the Hemodynamic Impact of Anterior Leaflet Laceration in Transcatheter Mitral Valve Replacement: An in silico Study - Kohli, Keshav; Wei, Zhenglun Alan; Sadri, Vahid; Siefert, Andrew W.; Blanke, Philipp; Perdoncin, Emily; Greenbaum, Adam B.; Khan, Jaffar M.; Lederman, Robert J.; Babaliaros, Vasilis C.; Yoganathan, Ajit P.; Oshinski, John N. (Frontiers in Cardiovascular Medicine, 2022)
Background A clinical study comparing the hemodynamic outcomes of transcatheter mitral valve replacement (TMVR) with vs. without Laceration of the Anterior Mitral leaflet to Prevent Outflow Obstruction (LAMPOON) has never been designed nor conducted. Aims To quantify the hemodynamic impact of LAMPOON in TMVR using patient-specific computational (in silico) models. Materials Eight subjects from the LAMPOON investigational device exemption trial were included who had acceptable computed tomography (CT) data for analysis. All subjects were anticipated to be at prohibitive risk of left ventricular outflow tract (LVOT) obstruction from TMVR, and underwent successful LAMPOON immediately followed by TMVR. Using post-procedure CT scans, two 3D anatomical models were created for each subject: (1) TMVR with LAMPOON (performed procedure), and (2) TMVR without LAMPOON (virtual control). A validated computational fluid dynamics (CFD) paradigm was then used to simulate the hemodynamic outcomes for each condition. Results LAMPOON exposed on average 2 ± 0.6 transcatheter valve cells (70 ± 20 mm2 total increase in outflow area) which provided an additional pathway for flow into the LVOT. As compared to TMVR without LAMPOON, TMVR with LAMPOON resulted in lower peak LVOT velocity, lower peak LVOT gradient, and higher peak LVOT effective orifice area by 0.4 ± 0.3 m/s (14 ± 7% improvement, p = 0.006), 7.6 ± 10.9 mmHg (31 ± 17% improvement, p = 0.01), and 0.2 ± 0.1 cm2 (17 ± 9% improvement, p = 0.002), respectively. Conclusion This was the first study to permit a quantitative, patient-specific comparison of LVOT hemodynamics following TMVR with and without LAMPOON. The LAMPOON procedure achieved a critical increment in outflow area which was effective for improving LVOT hemodynamics, particularly for subjects with a small neo-left ventricular outflow tract (neo-LVOT).